Enhancing Visitor Experiences at Digital Museum Concept in Jakarta - WIASTUTI, Rachel Dyah; LESTARI, Nurul Sukma; TRIANA, Ika; MASATIP, Anwari; NGATEMIN, Ngatemin; MULYADI, Bejo (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.11.6(46).14, 2020)
This study aims to examine the digital compliance of museums in Jakarta towards the accessible information concept. Furthermore, this study also explores the millennials’ perception towards digital technology adoption for museum. Taman Mini Indonesia Indah website was employed to remark the research object. Hence, 18 museums were finalized as of this research object. Data was accumulated through direct field observation in all museums and interview with museum staff. Meanwhile, a survey with questionnaire was distributed to gather the digital technology and accessible information perception of the museum. Also, other accessibility information data was gathered through content analysis. The findings reveal accessible information compliance in term of printed material, digital document, audio visual content, website, application, self- service terminal, and signage. Findings also show that Museum Olahraga turns out to be the most compliance regarding its accessible information and providing digitalization facilities such as interactive digital signage, augmented reality, interactive video mapping, automatic display slider, interactive kiosk, and interactive light show. However, the result shows that only several museums comply with digital context. This research implication is to deliver the best practice for the museum to anticipate future trends to ensure better experiences for the visitors.